KEBIJAKAN TAX AMNESTY DALAM PERSPEKTIF EKONOMI ISLAM Studi Kasus di KPP Pratama Langsa - fasya fasya (IAIN Langsa, 2017)
This research was aimed to find out the management of the implementation of the tax amnesty service in KPP Pratama Langsa, the constraints of the tax amnesty implementation in KPP Pratama Langsa, the impact of the tax amnesty implementation towards in increasing tax revenues and its relevance with economic of Indonesia and the tax amnesty policy in accordance with the Islamic economic perspective. The research used a qualitative approach. In this research, the researcher uses the field research and library research method. The location of research is KPP office Pratama Langsa. The results of research concluded that in the implementation of the tax amnesty policy, KPP Pratama has some procedures and constraints. The method of data is library research, interview, and document, by populasi and sample used snowball sampling. The tax amnesty policy impacting to increasing tax revenues and the economic of Indonesia, and also the tax amnesty policy in accordance with the Islam perspective because it's in accordance with the principles of Islamic economic such as the basic law of muamalah is Mubah, to make easy and facilitate not to make difficulty, and it is the principles of maslahah.